2005
DOI: 10.1128/jvi.79.12.7349-7354.2005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Virus Load by Highly Active Antiretroviral Therapy in Rhesus Macaques Infected with a Recombinant Simian Immunodeficiency Virus Containing Reverse Transcriptase from Human Immunodeficiency Virus Type 1

Abstract: We have modeled highly active antiretroviral therapy (HAART) for AIDS in rhesus macaques infected with a chimera (RT-SHIV) of simian immunodeficiency virus containing reverse transcriptase from human immunodeficiency virus type-1 (HIV-1). Seven RT-SHIV-infected macaques were treated with a combination of efavirenz (200 mg orally once daily), lamivudine (8 mg/kg subcutaneously once daily), and tenofovir (30 mg/kg subcutaneously once daily). Plasma viral RNA levels in all animals were reduced by more than 1,000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 41 publications
3
84
0
Order By: Relevance
“…Experiments with RT-SHIV mac239 , a direct antecedent to RT-SHIV mne , first demonstrated that substitution of SIV RT with HIV-1 RT yielded a virus with the desirable characteristics of robust replication within animals and susceptibility to antiviral agents which structurally recognize an HIV-1 protein (44,51). We developed a similar infection model with pigtail macaques to investigate questions of viral dynamics and the evolution of drug resistance in response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with RT-SHIV mac239 , a direct antecedent to RT-SHIV mne , first demonstrated that substitution of SIV RT with HIV-1 RT yielded a virus with the desirable characteristics of robust replication within animals and susceptibility to antiviral agents which structurally recognize an HIV-1 protein (44,51). We developed a similar infection model with pigtail macaques to investigate questions of viral dynamics and the evolution of drug resistance in response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An AIDS-like disease was first noted in rhesus macaques infected with SIV from sooty mangabeys (29). Although SIV infection of macaques is an excellent model for HIV-1 pathogenesis, it has only recently been used to model the treatment of HIV-1 infection (11,34,47,57), including the SIV/macaque model that we recently developed to study HIV latency under suppressive therapy (47). We showed that SIV established latent infection in resting macaque CD4…”
mentioning
confidence: 99%
“…In an animal model, antiretroviral suppression should be as good as what is observed in humans on combination antiretroviral therapy. Standard assays detect down to 50 copies of viral RNA per milliliter of plasma, but even with typical three drug regimens it has been difficult to completely inhibit plasma viremia in some macaques to undetectable levels (Ambrose et al, 2007;Dinoso et al, 2009;Lugli et al, 2011;North et al, 2005). The ability to achieve complete suppression generally correlates with the level of plasma viremia prior to treatment, such that higher viral loads are more difficult to completely suppress (Kearney et al, 2011).…”
Section: Evaluating Viral Reservoirs During Antiretroviral Therapymentioning
confidence: 99%
“…Efavirenz monotherapy leads to the emergence of common resistance mutations that are seen in patients (Ambrose et al, 2007;Hofman et al, 2004). Efavirenz combined with tenofovir and FTC is a commonly prescribed combination therapy for HIV-infected individuals and was shown to be effective in reducing RT-SHIV plasma viremia in two species of macaques (Ambrose et al, 2007;North et al, 2005). Prior efavirenz resistance was shown to compromise combination therapy in one animal, leading to accumulation of FTC-resistant mutations in the virus and, ultimately, failure of therapy (Ambrose et al, 2007).…”
Section: Drug Resistancementioning
confidence: 99%